The importance of interfacial stress-affected zone in evading the strength-ductility trade-off of heterogeneous multi-layered composites. (January 2023) - Wu, Hao; Huang, Meng; Xia, Yiping; Li, Xuewen; Li, Rengeng; Liu, Chenglu; Gan, Weimin; Xiao, Tiqiao; Geng, Lin; Liu, Qing; Fan, Guohua
Highlights: The presence of the interfacial stress-affected zone was experimentally verified. The influence of the interfacial stress-affected zone in determining the mechanical properties of multi-layered composites was elucidated. The length scale of the interfacial stress-affected zone was 15 μm for the present Ti/Al layered composites. The strength and ductility of Ti/Al layered composites were optimally combined when the Al layer thickness was nearly twice that of the interfacial stress-affected zone. Abstract: The interfacial stress-affected zone (ISAZ), characterized by a stress gradient maximizing at the interface, is considered a key factor in determining the mechanical properties of heterogeneous multi-layered materials. In the past few decades, the ISAZ dimension has been routinely estimated by two-dimensional strain mapping or by computational modeling; accurate stress measurement remains technically challenging. In the present study, we confirmed the presence of the ISAZ and quantified the stress evolution process upon tension of Ti/Al multi-layered composites using in situ high-energy X-ray diffraction and in situ neutron diffraction. Our results demonstrated that the ISAZ spanned 15 μm and remained unchanged for the present model material, independent of the load and layer thickness. The length scale of 15 μm was closely correlated with the mechanical property in such a way that the model material exhibited the highest work hardening rate, the greatest uniform flow capacity, and the most dispersed crack distribution, only if the Al layer thickness was nearly twice the ISAZ size of 15 μm. Under that condition, the soft Al layer was almost fully occupied by two adjacent ISAZs, and such a perfectly-coated stress distribution may enable a more efficient interfacial constraint effect to achieve superior mechanical properties. The present study therefore opens a new window to optimize the mechanical properties by tailoring the layer thickness according to the ISAZ scale.